The Health Professions: developments in legislation and training, from student application to employment - Mastrillo, Angelo (Acta Biomedica Atenei Parmensis, 2015)
Background and aim: The legislation and training of health workers have undergone various changes during the course of the last 90 years. In addition to the Degrees in Medicine and Surgery, and in Dentistry, with a duration of six years, the Faculty of Medicine and Surgery also offers three-year degree courses in the 22 health professions, including Nursing, Obstetrics, Physiotherapy, Speech Therapy, Laboratory work, Radiology, Neurophysiopathology and Dietetics. Method: A data research study was carried out over the last 18 years, on the legislation and training requirements for health workers, including the availability of University places and the applications presented, as well as the number of university lecturers and the employment opportunities. Results: Data reveal a steady increase from 1997 to 2011 in the number of student admission applications for Medicine and Surgery as well as for the other Health Professions, reaching a peak in 2012 and currently continuing to fall. The trend is different for lecturers, who, apart from a slight increase up to 2008, have remained at around 9400 in number since 1997. Conclusions: The drop in applications for places would appear to be linked to the fall in employment in the last six years, from 86% in 2007 to 62% in 2012. Although the health sector is still in first place among all the other sectors, careful reflection would seem to be warranted on the part of the Regions and the Ministries of Health and University Education when defining the annual training requirements for each of the 22 Health Professions